Inhaled Sedation for Invasively Ventilated COVID-19 Patients: A Systematic Review - Landoni, Giovanni; Belloni, Olivia; Russo, Giada; Bonaccorso, Alessandra; Carà, Gianmarco; Jabaudon, Matthieu (Journal of clinical medicine, 2022)
Background: Volatile anesthetics were used as sedative agents in COVID-19 (Coronavirus Disease 2019) invasively ventilated patients for their potentially beneficial pharmacological effects and due to the temporary shortages of intravenous agents during the pandemic crisis. Methods: Online databases (PubMed, EMBASE, The Cochrane Central Register of Controlled Trial) and the “clinicaltrials.gov” website were searched for studies reporting the use of isoflurane, sevoflurane or desflurane. Results: We identified three manuscripts describing the beneficial effects of isoflurane on 41 COVID-19 patients with acute respiratory distress syndrome (ARDS) in Germany (n = 2) and in the USA (n = 1), in terms of reduction in the use of opioids and other sedatives. We also found a case report of two patients with transient nephrogenic diabetes insipidus, which started after 6 and 8 days of sevoflurane sedation. We identified two randomized controlled trials (RCTs; 92 patients overall), two observational studies (238 patients) on the use of volatile anesthetics in COVID-19 patients that were completed but not yet published, and one RCT interrupted for a low recruitment ratio (19 patients) and thus not published. We also identified five ongoing RCTs on the use of inhaled sedation in ARDS, which are also likely to be recruiting COVID-19 patients and which have currently enrolled a total of >1643 patients. Conclusion: Isoflurane was the most frequently used volatile agent in COVID-19 patients and allowed a reduction in the use of other sedative and analgesic drugs. Randomized evidence is building up and will be useful to confirm or challenge these findings.